Short-term effects of surgical weight loss after sleeve gastrectomy on sex steroids plasma levels and PSA concentration in men with severe obesity. (9th April 2021) - Di Vincenzo, Angelo; Silvestrin, Valentina; Bertoli, Eleonora; Foletto, Mirto; Pagano, Claudio; Fabris, Roberto; Vettor, Roberto; Busetto, Luca; Rossato, Marco
Abstract: Male obesity is known to be associated with hypogonadism, which can be reverted after surgical weight reduction. However, the evidence about how rapidly this effect rises after surgery and what consequences each procedure have on prostate function and prostatic-specific antigen (PSA) concentration is scarce. So, we evaluated total testosterone, estradiol, luteinizing hormone, follicle-stimulating hormone and PSA plasma levels in a group of 29 Caucasian obese men (BMI - 43.4 ± 8.5 kg/m 2 ) before and one month after sleeve gastrectomy. 19 lean healthy male subjects were considered as controls. As expected, obese patients showed a high prevalence of hypogonadism (51.6%) at baseline, with reduced total testosterone compared to lean controls (10.8 ± 3.5 vs 15.7 ± 4.2 nmol/l, p < .01), higher estradiol (124.4 ± 46.5 vs 78.7 ± 39.6 pmol/l, p < .01), lower luteinizing hormone and follicle stimulating hormone (3.6 ± 1.3 and 2.5 ± 0.9 vs 5.2 ± 2.4 and 5.9 ± 3.8 U/L, respectively, p < .05) plasma levels. One month after surgery, patients showed a significant body weight reduction (−17.2 ± 6.7 kg) with increased total testosterone (from 10.8 ± 3.5 to 18.9 ± 4.9 nmol/l, p < .001), reduced estradiol (from 124.4 ± 46.5 to 96.1 ± 34.3 pmol/l, p < .05) and increased PSA (from 0.74 ± 0.38 to 1.0 ± 0.51 μg/l, p < .001). These results confirm that hypogonadism is highly prevalent in obese males, but they also show that it can be early reversed after sleeve gastrectomy, further confirming the strong indication to surgery of hypogonadal patients with severely reduced quality of life. Higher testosterone levels may be responsible for the increase of PSA observed after surgery; however, PSA concentration has to be monitored over time to avoid underrating of potential severe prostate diseases.